3.7k views
5 votes
Y= (x-9) (x+3)

I need to solve this using DETAILED step by step explanations. I need every step explained down to the "T" as if I were explaining it to someone who had no clue what they were doing...

1 Answer

5 votes

Answer:

y = x² − 6x − 27

Explanation:

To distribute, you can use something called FOIL. It stands for First, Outer, Inner, Last.

First, multiply the First term in each factor.

x · x = x²

Now multiply the Outer terms in each factor.

x · 3 = 3x

Next multiply the Inner terms in each factor.

-9 · x = -9x

Finally, multiply the Last terms in each factor.

-9 · 3 = -27

Add them all up:

x² + 3x − 9x − 27

x² − 6x − 27

User Beamie
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.